Komparasi Pergerakan Saham Apple Dan Samsung Menggunakan Algoritma Support Vector Machine (SVM) - Falentino Sembiring; Mayang Gunawan; Rosalinda Hakim; Vemi Januarita Putri (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The capital market creates opportunities for the public to participate in economic activities, especially in investing. One of the assets for investment is stock. The capital market creates opportunities for the public to participate in economic activities, especially in investing. One of the assets for investment is stock. The purpose of this research is to compare stock price movements between Apple companies and Samsung companies after the pandemic. One method that can be used to predict stock price movements is the support vector machine (SVM). This study uses two approaches as input models, the first approach for data input is obtained from the calculation of ten technical parameter indicators using trading data (open, high, low, close, price) while the second approach focuses on stating the results of calculations using several indicators Technical parameters become trend deterministic data preparation. Even this research uses historical data from each company from 2017 to 2022. This data is used to study patterns that can ultimately predict stock price movements of each company. From the results of this study with the help of Orange software, it can be concluded that the application states that in terms of data, Samsung's ROC analysis is 0.435% superior to Apple, only 0.359%.